Structural color nano-composite hard decorative coating and preparation process thereof
By co-depositing the composite structure of nanocrystalline aluminum nitride and amorphous silicon nitride in nitrogen and argon, the problem of color adjustment and hardness of hard coatings in the prior art is solved, and high hardness and multi-color adjustability are achieved The effect of the harmful blue light transmittance is weakened, protects vision and improves color rendering.
Patent Information
- Application Number
- CN202411364533.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to flexibly adjust the color of the transparent hard coating while maintaining high hardness, and the hardness of the oxide film is generally less than 10 GPa and has a low deposition rate.
The aluminum target and silicon target with DC power are co-deposited in nitrogen and argon, combined with the substrate bias, and prepared a hard coating of nanocrystalline aluminum nitride and amorphous silicon nitride composite structure through specific components, chemical bonds and The phase structure achieves adjustable effects of multiple structural colors.
It achieves high hardness (23.0~27.5GPa) and adjustable colors of various structures, while reducing the transmittance of harmful blue light in the short-band, protecting vision and improving the clarity and authenticity of color rendering.
Smart Images

Figure CN119243084A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of decorative films, and in particular to a structural color nano composite hard decorative coating and a preparation process thereof. Background Art
[0002] With the advent of the 5G era, smart electronic devices are undergoing a comprehensive upgrade from chips to forms, and their portability, lightness, impact resistance, heat dissipation and other properties have also received more and more attention. In addition to paying attention to functions, consumers will also pay attention to the color, pattern, gloss, lines, texture, feel, roughness and other aspects of the appearance. Among them, color is the primary factor in enhancing visual impact. It can easily allow consumers to understand the attributes of the product and stimulate visual resonance. It is a key factor directly related to whether the product has good market potential. At present, the colors of thin films mainly include pigment color and structural color. Among them, pigment color is caused by the selective absorption of visible light by the specific chemical structure of the pigment molecules contained in the object. It is usually accompanied by chemical pigments, which pollutes the environment. As the chemical structure changes or is destroyed, the color will change or disappear. Structural color is produced by the interference, diffraction, and scattering of light by the special physical structure of an object. It has advantages that many pigment colors do not have, such as high brightness, high saturation, polarization effect, iridescence effect, and never fading. It also has photochemical stability. As long as the physical structure of the material itself is not destroyed, its color will not fade.
[0003] The color of the pigmented decorative film depends on the electronic structure of the film material. At present, vacuum ion plating technology cannot calculate or design the corresponding electronic structure of the material to obtain the specified color, nor can it be expected to easily find the corresponding target material and reaction gas. At the same time, the physical and chemical behavior of the plasma in the ion plating process is not well understood. The decomposition and ionization of multi-element substances in the ion plating process, the various intermediate product forms and valence states, the number, proportion, energy and distribution of various particles in space, and how they are related to the electrical parameters of the plasma discharge, the emission source (target) and the conditions of the reaction gas supplied are not well understood. Therefore, it will take a long time of exploration and research to control the colors they need to synthesize.
[0004] In recent years, based on the principle of thin film interference structure coloring, the research on the structural coloring of oxide thin films deposited by magnetron sputtering has increased. Zhang et al. (Ceramics International, 2020, 46 (9): 13342-13349) formed a uniform and bright structural color on the fabric substrate by precisely controlling the thickness of the Ag2O film layer. Peng et al. constructed TiO2 / Cu / TiO2 thin films on polyester fabrics (Journal of Materials Science-Materials in Electronics, 2018, 29 (19): 16188-16198), and obtained green, yellow, brown and purple structural colors by changing the sputtering time of Cu. Yuan et al. coated Al / TiO2 and Ag / ZnO composite films on polyester woven fabrics (International Journal of Clothing Science and Technology, 2019, 31 (4): 487-494), and obtained purple, blue, blue-green and yellow structural colors. However, the hardness of oxide films is generally less than 10 GPa and the deposition rate is low (<0.5 nm / min). In the previously disclosed patent document CN117721428A, the inventor disclosed a transparent hard coating and preparation process that can reduce blue light. Through the co-deposition of aluminum targets and silicon targets in a magnetron sputtering system, a transparent hard coating with a density of up to 22.94 GPa can be prepared, and the deposition rate is relatively high, reaching 3.6 nm / min. However, the color rendering effect of the transparent hard coating is relatively single, and it is impossible to flexibly adjust the coating color according to the desired visual effect.
[0005] In summary, there is an urgent need to provide a new type of transparent hard coating and preparation process, which can flexibly adjust the coating color according to the desired visual effect while having high hardness. Summary of the invention
[0006] The purpose of the present invention is to provide a structural color nano-composite hard decorative coating and a preparation process, which can flexibly adjust the coating color according to the required visual effect while having high hardness.
[0007] In the first aspect, the present invention provides a structural color nano-composite hard decorative coating, which includes nanocrystalline aluminum nitride and amorphous silicon nitride. The crystal plane structure of the nanocrystalline aluminum nitride includes (100), (101), (102), (110) and (112) crystal planes. The elemental components of the coating, calculated by the atomic ratio of the elemental components of the coating, include: aluminum: 25-45at.%, silicon: 5-15at.%, nitrogen: 50-65at.%, and the sum of the elemental components is 100at.%.
[0008] Optionally, the ratio of the diffraction peak intensities of the (100) crystal plane and the (101) crystal plane of the nanocrystalline aluminum nitride is greater than 0.5.
[0009] Optionally, the molar ratio of SiN to AlN in the coating is 0.7 to 1.8, calculated based on the atomic ratio of N-Al bonds to N-Si bonds.
[0010] Optionally, the Al / N atomic ratio of the coating is 0.4 to 0.65.
[0011] Optionally, the hardness of the coating is 23.0 to 27.5 GPa.
[0012] Optionally, the coating has a blue light transmittance of 68.1-82.2% at 415-455 nm, a blue light transmittance of 72.3-89.7% at 455-500 nm, and a remaining visible light transmittance of 76.2-91.7% at 600-650 nm.
[0013] Optionally, the coating has a thickness of 186-460 nm.
[0014] In a second aspect, the present invention provides a preparation process for the aforementioned structural color nano-composite hard decorative coating, comprising the following preparation steps: placing a substrate in a chamber of a magnetron sputtering system, introducing argon and nitrogen after evacuation, turning on the DC power supply of the aluminum target and the silicon target and the bias power supply of the substrate for co-deposition, and preparing the structural color nano-composite hard decorative coating.
[0015] Optionally, the DC power supply power of the aluminum target is 200-400W, the DC power supply power of the silicon target is 10-130W, the bias power supply power of the substrate is 10-80W, the flow rate of the argon gas is 10-80sccm, and the flow rate of the nitrogen gas is 3-30sccm.
[0016] Optionally, the DC power supply power of the aluminum target is 250-350W, the DC power supply power of the silicon target is 20-120W, the bias power supply power of the substrate is 30-70W, the flow rate of the argon gas is 30-50sccm, and the flow rate of the nitrogen gas is 5-20sccm.
[0017] In summary, the present invention has the following beneficial effects:
[0018] 1. The present invention provides a structural color nano-composite hard decorative coating and a preparation process thereof. Aluminum targets and silicon targets of a direct current power supply are co-deposited in nitrogen and argon. Combined with a substrate bias, a hard coating composited with nanocrystalline aluminum nitride and amorphous silicon nitride can be prepared. The two act synergistically to further improve the hardness of the coating. In addition, the purpose of increasing the adjustable window range of the coating thickness can be achieved, so that the hardness of the coating with a thickness of 186 to 460 nm can reach more than 23.0 GPa. Based on the principles of nano-composite and thin film interference, the adjustable effects of various structural colors can be achieved, thereby satisfying the colorful visual decorative effect of the transparent hard coating.
[0019] 2. The present invention provides a structural color nano-composite hard decorative coating and a preparation process, which can prepare a hard coating with specific composition, chemical bonds, physical phase structure and thickness. It has different reflectivity and transmittance for visible light in different bands. On the basis of achieving adjustable multi-structural colors, it can also controllably weaken the transmittance of harmful blue light in the short-wave band. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 is a schematic cross-sectional view of a substrate and a coating according to an embodiment of the present invention;
[0022] Figure 2 The following are photos of the sample coatings of the present invention, (a) Examples 1-2 and Comparative Examples 1-2 with glass as the substrate, (b) Examples 1-2 and Comparative Examples 1-2 with silicon wafer as the substrate, (c) Examples 3-7 with glass as the substrate, (d) Examples 3-7 with silicon wafer as the substrate;
[0023] Figure 3 The chemical composition diagram of the coating of the samples of Example 1-2 and Comparative Example 1-2 of the present invention, (a) XPS full element scanning diagram, (b) element content diagram;
[0024] Figure 4 This is a fitting diagram of the XPS nuclear level spectrum of nitrogen element in the coating of the samples of Example 1-2 of the present invention and Comparative Example 1-2;
[0025] Figure 5 It is the GIXRD diffraction pattern of the sample coating of Examples 1-2 and Comparative Examples 1-3 of the present invention;
[0026] Figure 6The curves of the reflectivity of the sample coatings of the present invention as a function of the wavelength of visible light are (a) Examples 1-2 and Comparative Examples 1-2, (b) Examples 3-7;
[0027] Figure 7 The curves of the transmittance of the sample coatings of the present invention versus the wavelength of visible light are (a) Examples 1-2 and Comparative Examples 1-3, (b) Examples 3-7;
[0028] Figure 8 1 is a curve of the loading pressure of the sample coating of the present invention versus the indentation depth, (a) sample coatings of Examples 1-2 and Comparative Examples 1-2, (b) Examples 3-7;
[0029] Fig. 9 1 is a curve of the hardness of the sample coating of the present invention versus the indentation depth, (a) sample coatings of Examples 1-2 and Comparative Examples 1-2, (b) Examples 3-7.
[0030] Explanation of reference numerals: 10, substrate; 20, coating. DETAILED DESCRIPTION
[0031] The present invention provides a structural color nano-composite hard decorative coating and a preparation process. In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. It should be noted that the directional terms such as upper, lower, left, right, front, back, inside, and outside that appear or are about to appear in the text of the present invention are based only on the drawings of the present invention, and are not specific limitations of the present invention.
[0032] The inventor disclosed a transparent hard coating and preparation process that can reduce blue light in the previously disclosed patent document CN117721428A. The reactive magnetron sputtering technology is used to deposit a transparent hard coating with a single-layer structure on the surface of the substrate. The element doping and thin film interference principle are used to achieve a good effect of reducing the blue light transmittance. The prepared coating has a hardness of up to 22.94GPa. At the same time, by adjusting the process parameters of magnetron sputtering, the ratio of SiN and AlN can be accurately adjusted, and then the transmittance of the coating to different wavelengths of blue light and other visible light can be adjusted. The controllability is strong, especially reducing the transmittance of harmful blue light in the short-wave band, protecting eyesight. However, the transparent hard coating prepared by the preparation process has a relatively single color, which is difficult to meet the needs of the decorative coating to flexibly adjust the color of the coating according to the visual effect, and the adjustable window range of the high-hardness coating thickness is narrow, with a thickness of 200 to 240nm. When the thickness of the coating is reduced or increased, the hardness of the coating decreases, and it is difficult to meet the interference of thin films of different thicknesses to achieve a color-adjustable visual effect. After long-term experimental research, the inventors surprisingly found that by using a direct current power supply to co-deposit an aluminum target and a silicon target in nitrogen and argon, combined with a substrate bias, a transparent hard coating including a specific composite structure of aluminum nitride and silicon nitride can be prepared on the substrate, wherein the aluminum nitride is formed as nanocrystals and the silicon nitride is formed as an amorphous phase. The amorphous silicon nitride is wrapped around the aluminum nitride grain boundaries, which hinders the growth of grains and refines the coating grains. The two work synergistically to improve the hardness of the coating. In addition, the dense hard coating composed of specific components, chemical bonds and phase structures can also increase the thickness adjustable window range of the high-hardness coating. Based on the interference principle of nano-composite and thin films of different thicknesses, the adjustable effect of multiple structural colors is achieved, thereby satisfying the colorful visual decorative effect of the transparent hard coating.
[0033] It is worth mentioning that in some embodiments of the present invention, the prepared transparent hard coating also reduces the transmittance of harmful blue light in the short-wave band, achieving the effect of protecting eyesight, while maintaining a good transmittance for beneficial blue light in the long-wave band and other visible light, which is conducive to improving the clarity and authenticity of color rendering. The present invention is obtained on this basis.
[0034] In some embodiments of the present invention, a structural color nanocomposite hard decorative coating is provided, the coating comprising nanocrystalline aluminum nitride and amorphous silicon nitride, the crystal plane structure of the nanocrystalline aluminum nitride comprising (100), (101), (102), (110) and (112) crystal planes, and the elemental composition of the coating, in terms of atomic ratio of the elemental composition of the coating, comprises: aluminum: 25-45 at.%, silicon: 5-15 at.%, nitrogen: 50-65 at.%, and the sum of the elemental composition is 100 at.%. Preferably, aluminum: 25-40 at.%, silicon: 5-15 at.%, nitrogen: 50-65 at.%, more preferably, aluminum: 28-38 at.%, silicon: 5-13 at.%, nitrogen: 52-65 at.%, more preferably, aluminum: 30-35 at.%, silicon: 6-12 at.%, nitrogen: 55-64 at.%.
[0035] In some embodiments of the present invention, the nanocrystalline aluminum nitride has a preferred orientation in the (100) crystal plane, and the ratio of the diffraction peak intensity between the (100) crystal plane and the (101) crystal plane is greater than 0.5; preferably greater than 0.8; more preferably greater than 1; more preferably greater than 1.2 and less than 2.
[0036] In some embodiments of the present invention, the molar ratio of SiN to AlN in the coating is 0.7 to 1.8, calculated based on the atomic ratio of N-Al bonds to N-Si bonds.
[0037] In some embodiments of the present invention, the Al / N atomic ratio of the coating is 0.4-0.65.
[0038] In some embodiments of the present invention, the hardness of the coating is 23.0 to 27.5 GPa; preferably, the hardness of the coating is 24.0 to 27.5 GPa; more preferably, it is 25.0 to 27.5 GPa, and more preferably, it is 26.0 to 27.5 GPa.
[0039] In some embodiments of the present invention, the blue light transmittance of the coating at 415-455nm is 68.1-82.2%, the blue light transmittance at 455-500nm is 72.3-89.7%, and the remaining visible light transmittance at 600-650nm is 76.2-91.7%. Preferably, the blue light transmittance of the coating at 415-455nm is 70.2-77.8%, the blue light transmittance at 455-500nm is 77.8-89.7%, and the remaining visible light transmittance at 600-650nm is 84.8-91.7%.
[0040] In some embodiments of the present invention, the thickness of the coating is 186-460 nm.
[0041] In some embodiments of the present invention, a preparation process of the aforementioned structural color nano-composite hard decorative coating is provided, comprising the following preparation steps: placing a substrate in a chamber of a magnetron sputtering system, evacuating the chamber and introducing argon and nitrogen, turning on the DC power supply of the aluminum target and the silicon target and the bias power supply of the substrate for co-deposition, and preparing the structural color nano-composite hard decorative coating.
[0042] In some embodiments of the present invention, the DC power supply power of the aluminum target is 200-400W, the DC power supply power of the silicon target is 10-130W, the bias power supply power of the substrate is 10-80W, the flow rate of the argon gas is 10-80sccm, and the flow rate of the nitrogen gas is 3-30sccm.
[0043] In some embodiments of the present invention, the DC power supply power of the aluminum target is 250-350W, the DC power supply power of the silicon target is 20-120W, the bias power supply power of the substrate is 30-70W, the flow rate of the argon gas is 30-50sccm, and the flow rate of the nitrogen gas is 5-20sccm. Preferably, the DC power supply power of the aluminum target is 280-320W, the DC power supply power of the silicon target is 50-120W, the bias power supply power of the substrate is 30-70W, the flow rate of the argon gas is 30-50sccm, and the flow rate of the nitrogen gas is 5-20sccm. Preferably, the sputtering time is 10 to 500min, and more preferably, the sputtering time is 10 to 300min. The temperature of the co-deposition step of the present invention can be selected from room temperature to 300°C.
[0044] The present invention is described in detail below in conjunction with specific examples and comparative examples. In the following examples and comparative examples, transparent glass (electronic grade glass, the sample is square, the side length is 20 mm, and the thickness is 1.1 mm) and silicon wafer (100) are used as substrates, respectively, and magnetron sputtering technology is used for preparation. Figure 1 , depositing coating 20 on substrate 10. The substrate is placed in a chamber of a magnetron sputtering system and evacuated to 5×10 -6 Torr, before turning on the target gun power for deposition, argon gas is introduced, the argon gas flow rate is controlled to 40sccm, the RF bias is controlled to 100W, and the substrate surface is glow discharge cleaned for 10 minutes to remove contaminants on the substrate surface.
[0045] Example 1
[0046] After the substrate is glow discharge cleaned, at room temperature, the argon flow rate is maintained at 40sccm, and nitrogen is introduced at the same time, and the nitrogen flow rate is controlled to be 10sccm. Then the target gun power is turned on, and the DC power supply power of the aluminum target is controlled to DC300W, the DC power supply power of the silicon target is DC30W, and the substrate bias power is RF50W. Reactive sputtering is carried out for 83 minutes. After sputtering is completed, the sample A-1 is taken out to prepare the sample. The thickness of the coating of the sample A-1 is measured to be 460nm. For specific process parameters, please refer to Table 1. Table 1 is the process parameters of magnetron sputtering of the sample coatings of each embodiment and comparative example. It should be noted that each embodiment and comparative example uses transparent glass and silicon wafer as substrates respectively to prepare transparent hard coatings by the same process. Taking Example 1 as an example, the transparent glass and silicon wafer are placed in the chamber of the magnetron sputtering system at the same time, and cleaned and coated to prepare sample A-1. The sample A-1 is taken out, and the thickness of the transparent glass and silicon wafer substrates is measured to be the same, both 460nm. The film thickness shown in Table 1 is the thickness of the transparent hard coating prepared using transparent glass and silicon wafer as substrates, respectively.
[0047] Table 1. Process parameters of magnetron sputtering of sample coatings
[0048]
[0049]
[0050] Example 2
[0051] Referring to Table 1, the difference between Example 2 and Example 1 is that the DC power supply power of the silicon target in Example 2 is DC90W, and the remaining preparation steps are the same as those in Example 1. After sputtering, sample A-2 is prepared, and the coating thickness of sample A-2 is measured to be 445nm.
[0052] Example 3
[0053] Referring to Table 1, the difference between Example 3 and Example 2 is that the sputtering time of Example 3 is 55 minutes, and the remaining preparation steps are the same as those of Example 2. After the sputtering is completed, sample A-3 is prepared, and the coating thickness of sample A-3 is measured to be 300 nm.
[0054] Example 4
[0055] Referring to Table 1, the difference between Example 4 and Example 2 is that the sputtering time of Example 4 is 53 minutes, and the remaining preparation steps are the same as those of Example 2. After the sputtering is completed, sample A-4 is prepared, and the coating thickness of sample A-4 is measured to be 246 nm.
[0056] Example 5
[0057] Referring to Table 1, the difference between Example 5 and Example 2 is that the sputtering time of Example 5 is 42 minutes, and the remaining preparation steps are the same as those of Example 2. After the sputtering is completed, sample A-5 is prepared, and the coating thickness of sample A-5 is measured to be 208 nm.
[0058] Example 6
[0059] Referring to Table 1, the difference between Example 6 and Example 2 is that the sputtering time of Example 6 is 38 minutes, and the remaining preparation steps are the same as those of Example 2. After the sputtering is completed, sample A-6 is prepared, and the coating thickness of sample A-6 is measured to be 200 nm.
[0060] Example 7
[0061] Referring to Table 1, the difference between Example 7 and Example 2 is that the sputtering time of Example 7 is 33 minutes, and the remaining preparation steps are the same as those of Example 2. After the sputtering is completed, sample A-7 is prepared, and the coating thickness of sample A-7 is measured to be 186 nm.
[0062] Comparative Example 1
[0063] Referring to Table 1, the difference between Comparative Example 1 and Example 1 is that the DC power supply power of the silicon target in Comparative Example 1 is 0 W, the sputtering time is 120 min, and the remaining preparation steps are the same as those in Example 1. After sputtering, sample B-1 is prepared, and the coating thickness of sample B-1 is measured to be 476 nm.
[0064] Comparative Example 2
[0065] Referring to Table 1, the difference between Comparative Example 2 and Example 1 is that the DC power supply power of the silicon target in Comparative Example 2 is 150 W, and the remaining preparation steps are the same as those in Example 1. After sputtering, sample B-2 is prepared, and the coating thickness of sample B-2 is measured to be 780 nm.
[0066] Comparative Example 3
[0067] Referring to Table 1, the difference between Comparative Example 3 and Example 1 is that the aluminum target power supply of Comparative Example 3 is changed from DC to AC, the aluminum target power is 300 W, the silicon target power is 0 W, the substrate is not biased, the nitrogen flow rate is changed to 8 sccm, the coating time is adjusted to 60 min, and the remaining preparation steps are the same as those in Example 1. After sputtering is completed, sample B-3 is prepared, and the coating thickness of sample B-3 is measured to be 105 nm.
[0068] Figure 2 a is a physical picture of the samples of Examples 1, 2 and Comparative Examples 1, 2 with transparent glass as the substrate. Figure 2It can be seen from a that the coatings of samples A-1 and A-2 of Examples 1 and 2 are both lavender transparent coatings, sample B-1 of comparative example 1 is a light purple transparent coating, and sample B-2 of comparative example 2 is an opaque brown coating. Figure 2 b is a physical picture of the samples of Examples 1, 2 and Comparative Examples 1, 2 with silicon wafer as the substrate, Figure 2 It can be seen from b that the coatings of samples A-1 and A-2 of Examples 1 and 2 are both purple, the coating of sample B-1 of comparative example 1 is light purple, and the coating of sample B-2 of comparative example 2 is brown.
[0069] Figure 2 c is a physical picture of the sample of Example 3-7 with transparent glass as the substrate. Figure 2 As can be seen from Fig. 3, samples A-3, A-4, A-5, A-6 and A-7 of Examples 3-7 present red, green, cyan, blue and purple coatings respectively. Figure 2 d is a physical picture of the sample of Example 3-7 with a silicon wafer as the substrate, Figure 2 It can be seen from d that samples A-3, A-4, A-5, A-6, and A-7 of Examples 3-7 present red, green, cyan, blue, and dark purple coatings, respectively.
[0070] The elemental compositions in the examples and comparative examples of the present application were measured using an X-ray photoelectron spectrometer (XPS) from Thermo Fisher Scientific. Figure 3 a is the XPS test image of the sample coatings of Examples 1-2 and Comparative Examples 1-2 with silicon wafer as the substrate. The XPS test results show that the elemental composition detected in the sample coatings of Examples 1-2 and Comparative Example 2 includes Al, Si and N, as well as C and O. The elemental composition detected in the sample coating of Comparative Example 1 includes Al and N, as well as C and O. The elements detected in the sample coatings of Examples 3-7 and Example 2 are the same, and the elemental composition includes Al, Si and N, as well as C and O. Among them, the above-mentioned C and O elements all come from the air adsorbed on the surface of the sample coating when the sample is exposed to the air.
[0071] Figure 4 a is the nuclear energy curve fitting diagram of nitrogen element in the sample coatings of Examples 1, 2 and Comparative Examples 1, 2 with silicon wafer as the substrate. It can be seen that the sample coating of Comparative Example 1 contains N-Al bonds and NC bonds. N-Al bonds, N-Si bonds and NC bonds were detected in the sample coatings of Examples 1, 2 and Comparative Example 2. Among them, the above-mentioned NC bonds all come from the air adsorbed on the surface of the sample coating when the sample is exposed to the air. Table 2 shows the element content ratio of the samples of Comparative Examples 1-3 and Examples 1-2 and the content of each chemical bond in the N element.
[0072] Table 2. Element composition of sample coatings and the content of chemical bonds formed with nitrogen
[0073] Sample coating Al Si N N-Al N-Si NC Comparative Example 1 47.79 0 52.21 88.70 0 11.30 Comparative Example 2 33.88 16.74 49.38 26.50 64.98 8.52 Comparative Example 3 62.35 0 37.65 96.64 0 3.36 Example 1 30.70 6.75 62.55 55.18 41.86 2.96 Example 2 34.02 10.68 55.30 36.13 62.09 1.78
[0074] Analysis of XPS test results shows that ( Figure 3 b and Table 2), the Al / N atomic ratio in the coating of sample A-1 of Example 1 is 0.49, and the atomic ratio of silicon is 6.75%; the Al / N atomic ratio in the coating of sample A-2 of Example 2 is 0.62, and the atomic ratio of silicon is 10.68%; the Al / N atomic ratio in the coating of sample B-1 of comparative example 1 is 0.91, and the atomic ratio of silicon is 0; the Al / N atomic ratio in the coating of sample B-2 of comparative example 2 is 0.69, and the atomic ratio of silicon is 16.74%; the Al / N atomic ratio in the coating of sample B-3 of comparative example 3 is 1.66, and the atomic ratio of silicon is 0.00%.
[0075] Depend on Figure 4 b and Table 2, it can be seen that the atomic ratio of N-Si bonds and N-Al bonds in the coating of sample A-1 of Example 1 is 0.76, and the molar ratio of SiN and AlN in the coating is 0.76 based on the atomic ratio of N-Si bonds and N-Al bonds; the atomic ratio of N-Si bonds and N-Al bonds in the coating of sample A-2 of Example 2 is 1.72, and the molar ratio of SiN and AlN in the coating is 1.72 based on the atomic ratio of N-Si bonds and N-Al bonds; the atomic ratio of N-Si bonds and N-Al bonds in the coating of sample B-2 of comparative example 2 is 2.45, and the molar ratio of SiN and AlN in the coating is 2.45 based on the atomic ratio of N-Si bonds and N-Al bonds.
[0076] The same testing method as in Example 2 was used to test the coating element composition of Examples 3-7 and the content of chemical bonds formed with the nitrogen element. It was found that the coating element composition of Examples 3-7 and the content of chemical bonds formed with the nitrogen element were the same as those in Example 2.
[0077] The X-ray diffraction patterns of the silicon wafer substrate samples of the embodiments and comparative examples of the present application were tested using a D8Advance grazing incidence X-ray diffractometer from Bruker, Germany.
[0078] Depend on Figure 5 It can be seen that according to PDF#75-1620, the sample coating of Comparative Example 1 is a single-phase polycrystalline structure preferentially grown on AlN(101), and characteristic peaks such as AlN(100), (002), (102), (110), (103), (112), and (201) are all detected, among which the diffraction peak intensity of AlN(100) and (002) is much lower than the diffraction peak intensity of AlN(101).
[0079] The coating of the sample of Comparative Example 2 has become amorphous, indicating that the increase in silicon content causes AlN to become amorphous.
[0080] The sample coating of Comparative Example 3 is a single-phase polycrystalline structure preferentially grown on AlN(002), and characteristic peaks such as AlN(100), (101), (102), and (103) are detected. Among them, the diffraction peak intensity of AlN(100) and (101) is much lower than the diffraction peak intensity of AlN(002). In addition, due to the thin thickness of Comparative Example 3, according to PDF#01-0787, the characteristic peak (311) of the Si substrate is detected.
[0081] The characteristic peaks of AlN (100), (002), (101), (102), (110), (103), (200), (112) of the coating of the sample of Example 1 were all detected, but the characteristic peak of SiN was not detected, indicating that SiN existed in an amorphous form. Compared with the characteristic peaks of the coating of the sample of Comparative Example 1, the diffraction peak intensity of AlN (100) and (002) of the coating of the sample of Example 1 was significantly increased, and the ratio of the diffraction peak intensity of AlN (100) and (101) crystal planes was measured to be 0.55:1.
[0082] The characteristic peaks of AlN (100), (002), (101), (102), (110), (112) and the like of the coating of the sample of Example 2 were all detected, but the characteristic peak of SiN was not detected, indicating that SiN existed in an amorphous form. Compared with the characteristic peaks of the coating of the sample of Comparative Example 1, the diffraction peak intensity of AlN (100) of the coating of the sample of Example 2 was significantly increased, and the ratio of the diffraction peak intensity of the AlN (100) and (101) crystal planes was measured to be 1.21:1.
[0083] Using the same testing method as in Example 2, it was found that the phase structures of the sample coatings of Examples 3-7 and the crystal planes and intensities of the characteristic diffraction peaks were the same as those of Example 2.
[0084] The transmission spectra and reflection spectra of the samples of the embodiments and comparative examples of the present application (transmittance using glass substrate, reflectivity using silicon wafer substrate) were tested using a Cary5000 UV-visible-near infrared spectrophotometer from Agilent Technologies, USA. The baseline correction signal of the reflection spectrum comes from BaSiO4 powder without a thin film sample placed on it. The curves of the reflectivity of the sample coatings of embodiments 1-7 and comparative examples 1 and 2 as a function of the wavelength of visible light are shown in the figure below: Figure 6 Specific visible light reflectance data are shown in Table 3. Table 3 shows the visible light reflectance of the silicon substrate and the sample coatings of Examples 1-7 and Comparative Examples 1-2. The baseline correction signal of the transmission spectrum comes from an empty stage without a sample. The curves of the transmittance of the glass substrate sample coatings of Examples 1-7 and Comparative Examples 1-3 as a function of the visible light wavelength are shown in Table 3. Figure 7 As shown, the specific visible light transmittance data are shown in Table 4. Table 4 shows the hardness and visible light transmittance of the coatings of silicon wafers, glass substrates, and silicon wafer substrate samples of Examples 1-7 and Comparative Examples 1-2.
[0085] Table 3. Visible light reflectance of silicon wafer substrate and sample coating
[0086]
[0087]
[0088] Depend on Figure 6 As shown in Table 3, the reflectivity of the silicon wafer substrate to visible light in each band is similar, with no significant difference, and the reflectivity is about 60.0%. It can be seen that the silicon wafer substrate cannot display the color of a certain band and appears gray.
[0089] The coating of the sample of Comparative Example 1 has a maximum reflectivity of 76.2% at 386nm in the violet band (350-420nm), a second highest reflectivity of 69.0% at 474nm in the blue band (420-520nm), and a third highest reflectivity of 66.9% near 622nm in the remaining bands (550-650nm). This shows that the color presented by Comparative Example 1 is purple, which is different from Figure 2 It is consistent with what is shown in Figure b.
[0090] The visible light reflectance of the sample coating of Comparative Example 2 is similar in all bands below 600nm, with no significant difference. The reflectance is about 58.0%, and the highest reflectance is 60.1% near 720nm, indicating that the color of the coating is similar to red, that is, brown, which is also similar to red. Figure 2 It is consistent with what is shown in Figure b.
[0091] Example 1 has the highest reflectivity of 82.4% at 382nm in the violet band (350-420nm), the second highest reflectivity of 79.1% at 469nm in the blue band (420-520nm), and the third highest reflectivity of 78.2% at around 618nm in the remaining bands (550-650nm). This shows that the color presented by Example 1 is purple, which is consistent with Figure 2 It is consistent with what is shown in Figure b.
[0092] Example 2 has the highest reflectivity of 84.9% at 375nm in the violet band (350-420nm), the second highest reflectivity of 77.5% at 455nm in the blue band (420-520nm), and the third highest reflectivity of 75.6% at around 591nm in the remaining bands (550-650nm). This shows that the color presented by Example 2 is purple, which is consistent with Figure 2It is consistent with what is shown in Figure b.
[0093] Example 3 has a maximum reflectivity of 69.8% at 418nm in the violet band (350-420nm), no peak in the blue band (420-520nm), and a second highest reflectivity of 58.6% at around 614nm in the remaining band (550-650nm). This shows that the color presented by Example 3 is red, which is consistent with Figure 2 It is consistent with what is shown in Figure d.
[0094] Example 4 has a maximum reflectivity of 95.1% at 370nm in the violet band (350-420nm), no peak in the blue band (420-520nm), and a second highest reflectivity of 83.0% at around 540nm in the remaining bands (550-650nm). This shows that the color presented by Example 4 is green, which is consistent with Figure 2 It is consistent with what is shown in Figure d.
[0095] Example 5 has a maximum reflectivity of 86.3% at 365nm in the violet band (350-420nm), a second highest reflectivity of 73.1% at 513nm in the blue band (420-520nm), and no peaks in the remaining bands (550-650nm). This shows that the color presented by Example 5 is cyan, which is consistent with Figure 2 It is consistent with what is shown in Figure d.
[0096] Example 6 has no peak in the violet band (350-420nm), and has a maximum reflectivity of 89.0% at 446nm in the blue band (420-520nm), and no peak in the remaining bands (550-650nm). This shows that the color presented by Example 4 is blue, which is consistent with Figure 2 It is consistent with what is shown in Figure d.
[0097] Example 7 has a maximum reflectivity of 71.9% at 391nm in the violet band (350-420nm), no peak in the blue band (420-520nm), and no peak in the remaining bands (550-650nm). This shows that the color presented by Example 7 is purple, which is consistent with Figure 2 It is consistent with what is shown in Figure d.
[0098] Table 4. Hardness and visible light transmittance of silicon wafer, glass substrate and sample coating
[0099]
[0100] Depend on Figure 7 As shown in Table 4, the transmittance of the glass substrate to visible light in each band is similar, with no significant difference, and the transmittance is around 91.0%. It can be seen that the glass substrate cannot attenuate blue light.
[0101] The transmittance of the sample coating of Comparative Example 1 to harmful blue light is between 76.8% and 83.5%, the transmittance of beneficial blue light is between 80.7% and 91.2%, and the transmittance of the remaining visible light is between 84.4% and 90.9%. It can be seen that the sample coating of Comparative Example 1 can attenuate the blue light to a certain extent, and maintain the transmittance of beneficial blue light above 80.7%, and the transmittance of the remaining visible light above 84.4%.
[0102] The coating of the sample in Comparative Example 2 can significantly reduce the transmittance of harmful blue light, beneficial blue light and other visible light, making the coating of the sample in Comparative Example 2 brown and opaque.
[0103] The transmittance of the sample coating of Comparative Example 3 to harmful blue light is 88.1-89.9%, the transmittance of beneficial blue light is 88.5-89.9%, and the transmittance of the remaining visible light is between 86.0-88.5%. It can be seen that the sample coating of Comparative Example 3 cannot attenuate blue light.
[0104] The sample coating of Example 1 can significantly reduce harmful blue light, and the transmittance of harmful blue light in the short-wave band is 70.2-77.8%. At the same time, it can maintain a high transmittance of beneficial blue light in the long-wave band and other visible light, so that the beneficial blue light and the other visible light are maintained at 77.8-89.7% and 84.8-91.7% respectively, which achieves the reduction of harmful blue light and protects eyesight while maintaining a high transmittance of beneficial blue light and other visible light, which is beneficial to the clarity and authenticity of color rendering.
[0105] The sample coating of Example 2 can significantly reduce harmful blue light, with a harmful blue light transmittance of 68.1-82.2%. At the same time, it can transmit beneficial blue light and other visible light, so that the beneficial blue light and other visible light are maintained at 72.3-83.1% and 76.2-82.6%, respectively. This achieves the goal of reducing harmful blue light and protecting eyesight, while allowing the beneficial blue light and other visible light to maintain a relatively high transmittance, which is beneficial to the clarity and authenticity of color rendering.
[0106] The coating of the sample of Example 3 cannot reduce harmful blue light, and the transmittance of harmful blue light is 83.1-90.9%. At the same time, the transmittance of beneficial blue light is reduced, so that the transmittance of beneficial blue light is 76.1-83.1%. The transmittance of other visible light is not affected and remains at 89.0-91.2%.
[0107] The sample coating of Example 4 can attenuate harmful blue light to a certain extent, with a harmful blue light transmittance of 76.7-81.4%, while being able to transmit beneficial blue light and other visible light, keeping the beneficial blue light and other visible light at 76.7-82.1% and 79.5-85.7% respectively.
[0108] The sample coating of Example 5 can attenuate harmful blue light to a certain extent, with a harmful blue light transmittance of 75.8-79.4%, while being able to transmit beneficial blue light and other visible light, keeping the beneficial blue light and other visible light at 79.4-89.0% and 76.6-82.1% respectively.
[0109] The sample coating of Example 6 can attenuate harmful blue light to a certain extent, with a harmful blue light transmittance of 78.8-85.5%, while being able to transmit beneficial blue light and other visible light, keeping the beneficial blue light and other visible light at 80.7-85.5% and 71.2-72.5% respectively.
[0110] The sample coating of Example 7 cannot reduce harmful blue light, and the transmittance of harmful blue light is 85.7-91.7%. At the same time, it can transmit beneficial blue light and other visible light, so that the beneficial blue light and other visible light are maintained at 79.1-85.7% and 79.5-84.0% respectively.
[0111] The hardness of the silicon wafer substrate samples in the examples and comparative examples of the present application was measured using the continuous stiffness module of the G200 nanoindenter produced by KLA Corporation of the United States. Figure 8 a is the loading and unloading curves of the silicon wafer substrate, transparent glass substrate, examples 1 and 2 and comparative examples 1 and 2 sample coatings of the present invention. Figure 8 b is the loading and unloading curves of the sample coatings of Examples 3-7 of the present invention. Fig. 9 a is the curve of the surface hardness of the coating of the silicon wafer substrate, transparent glass substrate, Examples 1 and 2 and Comparative Examples 1 and 2 as a function of the indentation depth. Fig. 9 b is the curve of the surface hardness of the coating of the samples of Examples 3-7 of the present invention changing with the indentation depth. The specific hardness values are shown in Table 4.
[0112] From Table 4, Figure 8 , Fig. 9 It can be seen that the hardness of the silicon wafer substrate is 12.8 GPa, and the hardness of the glass substrate is 7.2 GPa. The hardness of the coatings of the samples of Comparative Examples 1-3 is better than that of the silicon wafer substrate and the glass substrate. However, the hardness of Comparative Example 3 is significantly lower than that of Comparative Example 1. This is because the DC power supply and the substrate bias of Comparative Example 1 work together to deposit a nanocomposite hard coating with a specific structure, thereby obtaining a higher hardness. The hardness of the coatings of the samples of Examples 1 and 2 is above 23.7 GPa, and the maximum hardness of the coating can reach 27.0 GPa, which is much higher than the substrate hardness.
[0113] Depend on Figure 2 c and 2d, the colors of the coatings of the samples of Examples 3-7 are red, green, cyan, blue, and purple, respectively, which proves that the coatings of the samples of the examples not only have high hardness, but also have the effect of coloring of the thin film interference structure. In some embodiments, the effect of reducing harmful blue light can be further achieved.
[0114] The transparent hard coating of the embodiment of the present application can be used alone as a decorative coating functional film, or as the outermost layer of a decorative coating functional film, to achieve display of different colors while improving the hardness of the film; in addition, some embodiments of the present invention can also achieve the technical effect of reducing blue light.
[0115] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A structural color nanocomposite hard decorative coating, characterized in that: The coating comprises nanocrystalline aluminum nitride and amorphous silicon nitride. The crystal plane structure of the nanocrystalline aluminum nitride comprises (100), (101), (102), (110) and (112) crystal planes. In terms of the atomic ratio of the elemental components of the coating, the elemental components of the coating comprise: aluminum: 25-45 at.%, silicon: 5-15 at.%, nitrogen: 50-65 at.%, and the sum of the elemental components is 100 at.%.
2. The structural color nanocomposite hard decorative coating according to claim 1, characterized in that: The ratio of the diffraction peak intensity of the nanocrystalline aluminum nitride (100) crystal plane and the (101) crystal plane is greater than 0.
5.
3. The structural color nanocomposite hard decorative coating according to claim 1, characterized in that: Calculated by the atomic ratio of N-Al bonds to N-Si bonds, the molar ratio of SiN to AlN in the coating is 0.7 to 1.
8.
4. The structural color nanocomposite hard decorative coating according to claim 1, characterized in that: The Al / N atomic ratio of the coating is 0.4 to 0.
65.
5. The structural color nanocomposite hard decorative coating according to claim 1, characterized in that: The hardness of the coating is 23.0-27.5 GPa.
6. The structural color nanocomposite hard decorative coating according to any one of claims 1 to 5, characterized in that: The coating has a blue light transmittance of 68.1-82.2% at 415-455nm, a blue light transmittance of 72.3-89.7% at 455-500nm, and a remaining visible light transmittance of 76.2-91.7% at 600-650nm.
7. The structural color nanocomposite hard decorative coating according to any one of claims 1 to 5, characterized in that: The thickness of the coating is 186-460 nm.
8. A process for preparing a structural color nanocomposite hard decorative coating, characterized in that: The method comprises the following preparation steps: placing a substrate in a chamber of a magnetron sputtering system, introducing argon and nitrogen after evacuation, turning on the direct current power supply of the aluminum target and the silicon target and the bias power supply of the substrate for co-deposition, and preparing the structural color nano-composite hard decorative coating.
9. The process for preparing the structural color nanocomposite hard decorative coating according to claim 8, wherein: The DC power supply power of the aluminum target is 200-400W, the DC power supply power of the silicon target is 10-130W, the bias power supply power of the substrate is 10-80W, the flow rate of the argon gas is 10-80sccm, and the flow rate of the nitrogen gas is 3-30sccm.
10. The process for preparing the structural color nanocomposite hard decorative coating according to claim 9, characterized in that: The DC power supply power of the aluminum target is 250-350W, the DC power supply power of the silicon target is 20-120W, the bias power supply power of the substrate is 30-70W, the flow rate of the argon gas is 30-50sccm, and the flow rate of the nitrogen gas is 5-20sccm.
